2010
DOI: 10.1007/s00404-010-1549-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the factors affecting the perinatal outcome of monochorionic diamniotic twins

Abstract: Further FLP treatment can be performed on twins with TTTS so that prognosis may be improved. Since the risk of discordant growth is significantly greater in twins of nulliparous women, they should be monitored more carefully than multiparous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The difference of chorionicity by the method of conception was consistent with a previous study (Murakami et al 2011). MD twins have a greater perinatal risk including twin-to-twin transfusion syndrome, growth discordance, and perinatal death (Dube et al 2002;Hack et al 2006;Skiadas et al 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The difference of chorionicity by the method of conception was consistent with a previous study (Murakami et al 2011). MD twins have a greater perinatal risk including twin-to-twin transfusion syndrome, growth discordance, and perinatal death (Dube et al 2002;Hack et al 2006;Skiadas et al 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Considering this relative shortage of NICU beds in Shiga, population-based studies of regional perinatal medical circumstances are indispensable (Koshida et al 2015). Although there are some perinatal center-based studies related to multiple pregnancies in Japan (Murakami et al 2011;Nakayama et al 2012), there have been no population-based studies of multiple-birth infants associated with their occupation of regional NICU beds.…”
Section: Introductionmentioning
confidence: 99%
“…As an incidental finding, this study showed a significantly higher prevalence of nulliparous women in the group complicated by late sIUGR or BW discordance. So far, only one small study, including 42 monochorionic twin pregnancies, reported this finding. In singletons, the association between parity and fetal growth restriction has been well demonstrated, and uterine artery Doppler is recommended for the screening of pre‐eclampsia and fetal growth restriction in high‐risk women.…”
Section: Discussionmentioning
confidence: 99%